Antibacterial Activity of Different Plant Extracts and Phenolic Phytochemicals Tested on Paenibacillus Larvae Bacteria - Liviu Mărghitaş (Scientific Papers Animal Science and Biotechnologies, 2011)
Paenibacillus larvae, a Gram-positive and spore-forming bacterium is responsible for American foulbrood disease inbees. The antimicrobial activity of different plant extracts and phenolic phytochemical was evaluated onPaenibacillus larvae bacteria. In addition possible correlation with antioxidant activity of the same plant extracts wasstudied. Extracts of the following plants were utilized: Achillea millefolium (yarrow), Ocimum basilicum (basil),Thymus vulgaris (thyme) and Urtica dioica (nettle). The extracts that showed antimicrobial activity were later testedto determine the Minimal Inhibitory Concentration (MIC). Although nettle present the lowest polyphenolic contentcompared with the other plant extracts, exhibit the highest antimicrobial activity, measured as the inhibition zoneusing Mueller-Hinton agar plates. Basil presented both polyphenolic content and antimicrobial activity at higherlevels, while thyme had the lowest antimicrobial activity, even it present high amount of polyphenols.